Kualitas Selai Lembaran Kombinasi Pektin Albedo Semangka (Citrullus vulgaris Schard) dan Filtrat Buah Kelengkeng (Dimocarpus longan) - Junior, Bekerpin; Pranata, Franciscus Sinung; Purwijantiningsih, L. M. Ekawati (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
Watermelon albedo is the skin of the pulp (mesocarp) that lies between the skin the outside (exocarp), and the center of the meat (endocarp). Watermelon colored albedo white, has a thick, and composed of pectin. Pectin is a fiber group which can soluble in water has a function as a thickener in foodstuffs. One of the product preparation which requires pectin is fruit leather. Albedo pectin sheet jam watermelon produces a less attractive aroma and taste, so combined with longan’s fruit filtrate which has an interesting aroma and taste, and has nutritional content that is beneficial to the body. The purpose of this research is to find out differences in the effect of the combination of pectin watermelon’s albedo and longan’s fruit filtrate on chemical, physical, and microbiological quality of sheet jam and determine the pectin combination watermelon’s albedo and longan’s filtrate just right for producing sheet jam with the best quality. Completely Randomized Design (CRD) with 4 combination treatment. pectin of watermelon’s albedo versus longan fruit filtrate, namely treatment A 0 : 3; treatment B 1 : 2; treatment C 1.5 : 1.5; and treatment D 2 : 1. The results showed that the combination of watermelon’s albedo pectin and longan fruit filtrate gave effect which significantly different from the quality of sheet jam include moisture content, pectin, ash, crude fiber, soluble fiber, total dissolved solids, vitamine C, total acid is titrated and yet giving the effect was not significantly different on the microbiological test of Total Plate Figures (ALT) and yeast mold figures. A fruit leather product with a combination of watermelon and albedo pectin longan’s fruit filtrate with ratio 1 : 2 gives the best quality in terms of chemical characteristics include water content of 7.73%, pectin 0.32%, ash 0.83%, crude fiber 1.66%, soluble fiber 2.19%, total dissolved solids 68.33%, vitamine C 21.12 mg / 100mg, and total acid titrated 0.03%, physical characteristics include texture 334.67 g, and the resulting colored sheet white. Microbiological characteristics include ALT of 1.42 log CFU / g, and yeast molds of 1.1 log CFU / g, and has fulfilled with National Standard.